Penerapan metode Analitycal Hierarchy Process (AHP) dalam menentukan keputusan pengembangan usaha coffee shop - Islachudin, Muhammad Usman (LP3M Universitas Putra Bangsa, 2025)
Coffee shop “XYZ” faces challenges in determining the appropriate business development strategy to sustain growth amid the intense competition in the coffee industry. This study aims to identify the most appropriate business development strategy for the “XYZ” coffee shop using the Analytical Hierarchy Process (AHP) approach. Primary data were collected through questionnaires administered to three directors as key informants, while the analysis was conducted using the Expert Choice application. The findings reveal that the main priority in business development is to increase the number of customers and enhance customer loyalty, with human resources, particularly baristas, emerging as the most influential factor. Baristas play a crucial role not only in ensuring product quality but also in delivering service experiences that directly affect customer satisfaction and loyalty. The overall synthesis highlights the opening of new branches outside the City and Regency of Tegal as the most appropriate development strategy, as it achieved the highest priority score. These results emphasize that successful business expansion relies not only on market penetration but also on strengthening internal factors, especially the quality of human resources. It is therefore recommended that coffee shop “XYZ” prioritize an expansion strategy by opening new branches outside Tegal while simultaneously strengthening barista competencies through training and improved service standards, thereby ensuring sustainable growth in customer acquisition and loyalty.